Telaah Pemikiran Fazlur Rahman tentang Epistemologi Hermeneutik dalam Pembaruan Hukum Keluarga Islam - Mohammad Arjati Firmansyah; Abdullah; M. Aunul Hakim (Al-Kindi, 2026)
This article examines hermeneutic epistemology in the reform of Islamic family law through an examination of Fazlur Rahman's thoughts. This study is motivated by the need for a methodological approach capable of bridging the tension between the normative text of the Qur'an and contemporary social dynamics in Islamic family law. This study aims to analyze the epistemological foundation of Fazlur Rahman's hermeneutics, explain the construction of the double movement method, and examine its implications for the reform of Islamic family law. This study uses a qualitative method based on literature studies with a philosophical-hermeneutic approach. Data were obtained from Fazlur Rahman's main works as primary sources and relevant scientific literature as secondary sources, which were analyzed using descriptive-conceptual, hermeneutic-philosophical, and critical-reflective techniques. The results show that Fazlur Rahman's hermeneutic epistemology positions the Qur'an as a source of universal moral values ​​that must be understood through the historical context of revelation and reactualized in a modern social context. The double movement method allows for a more substantive, contextual, and justice-oriented reconstruction of Islamic family law, particularly in issues of gender relations, marriage, and the protection of family rights. These findings confirm that Fazlur Rahman's thinking has made a significant contribution to the development of a methodology for reforming Islamic family law that is responsive to changing times without abandoning its normative foundation.